Implementasi Peraturan Daerah Kota Semarang Nomor 13 Tahun 2010 Tentang Penyelenggaraan Penanggulangan Bencana Pada Tahap Pra Bencana Di Kota Semarang. - Prima Mahardika Putra; Zainal Hidayat (Journal of Public Policy and Management Review, 2019)
Disaster management is a series of efforts which include the establishment of development policies that are at risk of disasters, disaster prevention activities, emergency response and rehabilitation. Disaster management is the responsibility of the central government and local government. The government handed over to the Regional Disaster Management Agency (BPBD) to deal with disasters in the region. One of the natural disasters that often hit Semarang was flooding. BPBD of Semarang uses Semarang City Regional Regulation Number 13 of 2010 concerning the Implementation of Disaster Management as the legal basis for implementing disaster management in the Semarang. The problem that arises is how the implementation of the regulation, especially pre-disaster stage. The purpose of this study was to determine the implementation of these regulations, especially at the pre-school stage and the factors that influence them. This study uses a descriptive qualitative research model with data analysis techniques from Miles and Huberman, and uses the source triangulation method to test the validity of the data. The results of this study indicate that the implementation of regulations, especially at the pre-disaster stage has not gone well. This can be seen from total eleven task, three of them weren’t done and the rest done with some problems. The implementation of regulation is influenced by factors of budget, coordination and resources that are in accordance with the theory put forward by Van Metter and Van Horn. The advices given is, first, the need for increased efforts in the implementation of activities that have been carried out so that there are no obstacles and carrying out activities that didn’t implemented yet. Second, it’s necessary to assess the factors that influence the implementation process.